2002
DOI: 10.1103/physrevd.65.125010
|View full text |Cite
|
Sign up to set email alerts
|

Self-gravitating domain walls and the thin-wall limit

Abstract: We analyse the distributional thin wall limit of self gravitating scalar field configurations representing thick domain wall geometries. We show that thick wall solutions can be generated by appropiate scaling of the thin wall ones, and obtain an exact solution for a domain wall that interpolates between AdS_4 asymptotic vacua and has a well-defined thin wall limit.Solutions representing scalar field configurations obtained via the same scaling but that do not have a thin wall limit are also presented.Comment:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 21 publications
0
88
0
Order By: Relevance
“…It can be shown that in this limit the energy-momentum tensor and all the curvatures converge rigourously to the corresponding tensor distributions associated to the RS thin brane geometry [12,21]), with singular parts which are proportional to a δ-distribution supported on the wall's plane. Now, it should be noticed that the scalar field (10) vanishes everywhere in the thin-wall limit δ → 0.…”
Section: B Domain Wall For a Sine-gordon Potentialmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be shown that in this limit the energy-momentum tensor and all the curvatures converge rigourously to the corresponding tensor distributions associated to the RS thin brane geometry [12,21]), with singular parts which are proportional to a δ-distribution supported on the wall's plane. Now, it should be noticed that the scalar field (10) vanishes everywhere in the thin-wall limit δ → 0.…”
Section: B Domain Wall For a Sine-gordon Potentialmentioning
confidence: 99%
“…Actually, following [12], it can be proved that (1,7) provides a sequence of metrics that satisfies the required convergence conditions of [4]. Then the distributional limit δ → 0 of all the curvature tensor fields of (1,7) exists and gives the curvatures of the limit metric.…”
Section: A the Kinkmentioning
confidence: 99%
See 2 more Smart Citations
“…Usual Newton's law can then be reproduced on the brane depending on the metric warp factor, attained after solving Einstein's equations. Several extensions soon appeared, with smooth thick branes constructed by scalar fields [7][8][9][10][11][12][13][14][15][16]. A comprehensive review on this subject can be found in [17].…”
Section: Introductionmentioning
confidence: 99%